1993
DOI: 10.1042/bj2950211
|View full text |Cite
|
Sign up to set email alerts
|

Differential responses of intestinal glucose transporter mRNA transcripts to levels of dietary sugars

Abstract: Dietary sugars are known to stimulate intestinal glucose transport activity, but the specific signals involved are unknown. The Na(+)-dependent glucose co-transporter (SGLT1), the liver-type facilitative glucose transporter (GLUT2) and the intestinal-type facilitative glucose transporter (GLUT5) are all expressed in rat jejunum [Miyamoto, Hase, Taketani, Minami, Oka, Nakabou and Hagihira (1991) Biochem. Biophys. Res. Commun. 181, 1110-1117]. In the present study we have investigated the effects of dietary suga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
104
0

Year Published

1997
1997
2014
2014

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 140 publications
(107 citation statements)
references
References 38 publications
3
104
0
Order By: Relevance
“…Among these facilitative hexose transporters, GLUT5 is unique in that it transports only fructose (7). High dietary fructose (but not glucose) content has been shown to directly increase intestinal expression of Glut5 in a rat model (8). The current study demonstrated that mRNA concentrations for six of seven GLUTs in diabetic muscle are not different from control subjects.…”
mentioning
confidence: 50%
“…Among these facilitative hexose transporters, GLUT5 is unique in that it transports only fructose (7). High dietary fructose (but not glucose) content has been shown to directly increase intestinal expression of Glut5 in a rat model (8). The current study demonstrated that mRNA concentrations for six of seven GLUTs in diabetic muscle are not different from control subjects.…”
mentioning
confidence: 50%
“…We showed that the SGLT1 mRNA contents of the jejunum and ileum were increased more in OLETF rats than in LETO rats. It has been reported that a high carbohydrate diet induces SGLT1 mRNA expression in a substrate-dependent manner [10]. The increment in intestinal SGLT1 mRNA in OLETF rats was considered to be independent of di-etary intake of carbohydrate since our study was undertaken in pair-feeding conditions.…”
Section: Discussionmentioning
confidence: 99%
“…If the glucose effect on fructose absorption is a result of transport, and not a result of solvent drag or a concentration gradient (32,33), then GLUT2 may be the best candidate for this effect (8,26). The effect whereby galactose, but not 3-O-methylglucose, improved fructose malabsorption was not anomalous with a role for GLUT2, given that although GLUT2 was shown to transport both galactose and 3-O-methylglucose, GLUT2 mRNA has been shown to be upregulated by glucose and galactose, but not by 3-O-methylglucose (40,47). Similarly, paracellular drag was invoked to explain glucose diffusion across the intestinal membrane beyond the capacity of the active glucose transporter SGLT1, which was saturated at 30 -50 mM glucose.…”
Section: Glucose Effect On Fructose Absorption In Humansmentioning
confidence: 99%
“…GLUT5 is a low-affinity, high-capacity fructose transporter that appears to be specific for fructose. Moreover, dietary fructose has been shown to upregulate GLUT5 mRNA expression (10,12,36,47). Transport of fructose across the basolateral membrane of gastrointestinal epithelial cells has been reported to utilize the facilitative hexose transporter GLUT2 (8).…”
Section: Transport Of Fructosementioning
confidence: 99%